Attitudes, beliefs and knowledge towards Medical Cannabis of Greek undergraduate and postgraduate university nursing students - Margarita Giannakopoulou; Fotini Vouzavali; Dimitra Paikopoulou; Antonia Paschali; Meropi D.A. Mpouzika; Maria N.K. Karanikola (Complementary Therapies in Medicine, 2021)
Objectives: To assess attitudes, beliefs and knowledge towards medical cannabis (MC) among Greek nursing students by year of study and undergraduate/postgraduate status. Methods: 294 (229 undergraduate and 65 postgraduate) students participated in this survey. Descriptive and inferential statistics (Pearson’s chi-squared, t-test) were applied using SPSS.24 (p ≤ 0.05). Results: Participant mean age (SD) was 23.1(6.6) years and 80.0 % of the study cohort was female. Senior undergraduate participants (3rd/4th year of study) reported more positive attitudes about MC benefits for mental health treatment compared to junior participants (1st/2nd year) (p = 0.017). Junior participants were more inclined to believe there are serious physical health risks associated with cannabis use (p = 0.038). Undergraduates, more than postgraduates, expressed a need for MC education and training for academic and practice purposes (p = 0.015); and, that there are physical and mental health risks associated with cannabis use (p = 0.007). Additionally, undergraduate nursing students were less likely than postgraduates to report knowledge about MC effectiveness for a variety of medical conditions (p ≤ 0.047); personal cannabis use for recreational purposes (p < 0.001); and, medical (p = 0.018) or recreational (p < 0.001) cannabis use among family members. The vast majority of all nursing students surveyed reported the need for formal education about MC (i.e., theoretical, clinical, laws and regulations) as part of their studies. Conclusion: Greek nursing student attitudes, beliefs and knowledge about MC vary according to year of study and undergraduate/postgraduate status. From this study, formal education on MC is recommended for Greek nursing students.